Galaninergic intramural nerve and tissue reaction to antral ulcerations. Issue 7 (2nd May 2018) - Zalecki, M.; Pidsudko, Z.; Franke‐Radowiecka, A.; Wojtkiewicz, J.; Kaleczyc, J.
Abstract: Background: Well‐developed galaninergic gastric intramural nerve system is known to regulate multiple stomach functions in physiological and pathological conditions. Stomach ulcer, a disorder commonly occurring in humans and animals, is accompanied by inflammatory reaction. Inflammation can cause intramural neurons to change their neurochemical profile. Galanin and its receptors are involved in inflammation of many organs, however, their direct participation in stomach reaction to ulcer is not known. Therefore, the aim of the study was to investigate adaptive changes in the chemical coding of galaninergic intramural neurons and mRNA expression encoding Gal, GalR1, GalR2, GalR3 receptors in the region of the porcine stomach directly adjacent to the ulcer location. Methods: The experiment was performed on 24 pigs, divided into control and experimental groups. In 12 experimental animals, stomach antrum ulcers were experimentally induced by submucosal injection of acetic acid solution. Stomach wall directly adjacent to the ulcer was examined by: (1) double immunohistochemistry—to verify the changes in the number of galaninergic neurons (submucosal, myenteric) and fibers; (2) real‐time PCR to verify changes in mRNA expression encoding galanin, GalR1, GalR2, GalR3 receptors. Key Results: In the experimental animals, the number of Gal‐immunoreactive submucosal perikarya was increased, while the number of galaninergic myenteric neurons and fibers (in all the stomach wall layers) remained unchanged. The expression of mRNA encoding all galanin receptors was increased. Conclusions & Interferences: The results obtained unveiled the participation of galanin and galanin receptors in the stomach tissue response to antral ulcerations. Abstract : The article describes the changes in the expression of galanin and its receptors in enteric neurons and tissues adjacent to stomach ulcer. Interestingly, an increase in the galanin expression in the submucosal plexus was not correlated with changes in the myenteric plexus neither near the ulcer (present results) nor in the pylorus. Moreover, the expression of all galaninergic receptors was increased in the tissues adjacent to the stomach ulcer. The present findings expand the knowledge on the participation of galaninergic system in ulcer disease.